Monetary regime change and business cycles - Vasco Cúrdia; Daria Finocchiaro (Federal Reserve Bank of New York, 2007)
This paper analyzes to what extent changes in monetary policy regimes influence the business cycle in a small open economy and investigates the impact of policy breaks on the estimation procedure. We estimate a dynamic stochastic general equilibrium (DSGE) model on Swedish data, explicitly taking into account the monetary regime change in 1993, from exchange rate targeting to inflation targeting. The results suggest that monetary policy reacted strongly to exchange rate movements in the former, and mostly to inflation in the latter. The external sector plays an important role in the economy, and the international transmission mechanism is significantly affected by the choice of exchange rate regime. A counterfactual experiment that applies the inflation targeting policy rule on the disturbances from the exchange rate targeting period suggests that such a policy would have led to higher output and employment, but also to a depreciated currency, higher inflation, and a more volatile economy. We also present evidence that ignoring the break in the estimation leads to spurious results for both the parameters associated with monetary policy as well as those that are policy-independent.
Keywords: C1; C5; E5; F4; 330; Bayesian estimation; DSGE models; target zone; inflation targeting; regime change; Geldpolitik; Inflation Targeting; Konjunktur; Dynamisches Gleichgewicht; Bayes-Statistik; Schweden